Pengaruh Lingkungan Kerja Dan Jenjang Karir Terhadap Loyalitas Karyawan Pada Kentucky Fried Chiken Makassar - Muhammad Zulfikar; Muhtazib Muhtazib; Mattarima Mattarima (Transformasi: Journal of Economics and Business Management, 2022)
This study was made to determine whether the influence of the work environment and career path on employee loyalty KFC Pettarani Makassar. This study has 3 variables, namely, work environment (X1), career path (X2), employee loyalty (Y). The study used data collection techniques through questionnaires from all respondents, namely 38 people, because respondents were less than 100 then the entire population was a sample. The data analysis conducted in this study is multiple linear analysis to see whether the work environment and career path have a partial or simultaneous effect on employee loyalty at KFC Pettarani Makassar. From the results of multiple linear analysis, it can be explained by the equation Y = 1.114 + 0.342X1 + 0.449X2 with a constant value of 1.114, meaning that if the work environment (X1) and career path (X2) are zero, then the work environment and career path are 1114. The regression coefficient of the work environment and career path of 0.342 and 0.449 means that the work environment and career paths have increased, so employee loyalty has also increased. And the value of Fcount > Ftable which is 31,814 > 1,739 also a significant value of 0.000 < 0.05 which means that the work environment and career path simultaneously (together) have an influence on employee loyalty.